Recent Advances in Modeling and Simulation Tools for Communication Networks and Services - Ince, A. Nejat; Bragg, Arnold; SpringerLink (Online service) (Boston, MA : Springer US, 2007)
This book contains a selection of papers presented at a Symposium organized under the aegis of COST Telecommunications Action 285. The main objective of the Action is to enhance existing modeling and simulation tools and to develop new tools for research in emerging multi-service telecommuncation networks in the areas of model performance improvement, multilayer traffic modeling, and the important issue of evaluation and validation of the new modeling tools. The studies related to the activities above are carried out by members of the Action Group with contributions from invited experts/scientists from non-COST countries, academia and industry (within and outside Europe). The book is a collection of important aspects of study results achieved by this distinguished group of experts/scientists from Europe and the US. The book is divided into the following six areas: - Multilayer Modeling - Wireless and Sensor Networks - Verification and Validation - High Throughput Systems - Traffic - Applications of Simulation A useful reference work for academic researchers and practitioners, this book is the third in a series of works focusing on modeling and simulation methods, techniques, and tools in telecommunications. Previous works in this series are: Modeling and Simulation Tools for Emerging Telecommunications Networks: Needs, Trends, Challenges and Solutions, by A. Nejat Ince and Ercan Topuz (editors), Springer, 2006, 510 pages, ISBN: 978-0-387-32921-5 Modeling and Simulation Environment for Satellite and Terrestrial Communications Networks, by A. Nejat Ince (Editor), Springer, 2004, 424 pages, ISBN: 978-0-7923-7547-0.
European Concerted Research Action COST 285 Action Objectives and the Symposium -- A Review of High Performance Simulation Tools and Modeling Concepts -- Using Visualization Techniques in Multilayer Traffic Modeling -- A Multilevel Approach for the Modelling of Large TCP/IP Networks -- Cross-Layer Interaction in Wireless Ad Hoc Networks: A Practical Example -- Multilayer Description of Large Scale Communication Networks -- Modelling and Simulation Study of TCP Performance with Link Layer Retransmission and Fragmentation for Satellite-UMTS Networks -- The Design of a FPGA-Based Traffic Light Control System: From Theory to Implementation -- Distributed Multihop Clustering Approach for Wireless Sensor Networks -- Scenario Simulation for Network-Centric Technology Assessment -- Verification and Validation of Simulation Models and Applications: A Methodological Approach -- Extending OPNET Modeler with External Pseudo Random Number Generators and Statistical Evaluation by the Limited Relative Error Algorithm -- Towards Flexible, Reliable, High Throughput Parallel Discrete Event Simulations -- Design and Performance Evaluation of a Packet-Switching Satellite Emulator -- Simulation Techniques for Peer-to-Peer Information Sharing Networks -- Repair Strategies on the Operation of MPLS Routing -- Incorporating Uncertainties into Traffic Simulators -- Effects of Bursty and Correlated Traffic on the Performance of Active Queue Management Schemes -- Quality-of-Service Analysis of Priority Queueing Systems under Long-Range Dependent and Short-Range Dependent Traffic -- Redimensioning Network Resources Based on Users' Behavior -- Internet Tomography in Support of Internet and Network Simulation and Emulation Modelling -- Emerging Requirements for Telecommunication Product Design and System Modeling -- A Tool for Packaging and Exchanging Simulation Results.
Keywords: Computer science; Computer organization; Computers; Computer Science; Computer Systems Organization and Communication Networks; Information Systems and Communication Service; Electronic books